Validation of the prognostic value of histologic scoring systems in primary sclerosing cholangitis: An international cohort study. - de Vries, E; de Krijger, M; Färkkilä, M; Arola, J; Schirmacher, P; Gotthardt, D; Goeppert, B; Trivedi, P; Hirschfield, G; Ytting, H; Vainer, B; Buuren, H; et al. (Wiley, 2016)
Histologic scoring systems specific for primary sclerosing cholangitis (PSC) are not validated. We recently determined the applicability and prognostic value of three histological scoring systems in a single cohort of PSC patients. The aim of this study was to validate their prognostic utility and reproducibility, using a well-characterized multicenter PSC cohort. Liver biopsies from PSC patients were collected across 7 European centers. Histologic scoring was performed using the Nakanuma, Ishak, and Ludwig scoring systems. Biopsies were independently scored by six liver pathologists for interobserver agreement. The prognostic value of clinical, biochemical, and all three histologic scoring systems on predicting composite endpoint 1: PSC-related death and liver transplantation, 2: liver transplantation, and 3: liver related events, were assessed using uni- and multivariable Cox proportional hazards modelling. 119 PSC patients were identified, The median follow-up was 142 months. During follow-up, 31 patients died (20 PSC-related deaths), 31 underwent liver transplantation, and 35 experienced one or more liver-related events. All three staging systems were independent predictors of endpoints 2 and 3; Nakanuma HR 3.16 (95%CI 1.49-6.68), HR 2.05 (95%CI 1.17-3.57); Ishak: HR 1.55 (95%CI 1.10-2.18), HR 1.43 (95%CI 1.10-1.85); Ludwig: HR 2.62 (95%CI 1.19-5.80), HR 2.06 (95%CI 1.09-3.89), respectively. Only the Nakanuma staging system was independently associated with endpoint 1: HR 2.14 (95%CI 1.22-3.77). The inter-observer agreement was moderate for Nakanuma stage (κ=0.56), and substantial for Nakanuma component fibrosis (κ=0.67), Ishak stage (κ=0.64) and Ludwig stage (κ=0.62). Conclusion We confirm the independent prognostic value and reproducibility of predicting disease progression in PSC by the Nakanuma, Ishak and Ludwig staging systems. The Nakanuma staging system – that incorporates features of chronic biliary disease – showed to hold the strongest predictive value.